130k views
1 vote
If s(x) = 2 – x2 and t(x) = 3x, which value is equivalent to (s.t) (-7)

User Bembas
by
5.3k points

2 Answers

3 votes
X would be it at least im pretty sure of it
User Joaocandre
by
4.1k points
2 votes

The product of the functions evaluated in x = -7 is 987

which value is equivalent to (s*t) (-7)?

To find this, we just need to find the product between the two functions evaluated in x = -7

s(x) = 2 - x²

Evaluating this in -7 we get:

s(-7) = 2 - (-7)²

= 2 - 49

= -47

For the other:

t(x) = 3x

t(-7) = 3*-7 = -21

The product gives:

(s*t) (-7) = s(-7)*t(-7) = -47*-21 = 987

User Jon Reeves
by
4.7k points